Local Product Development at Warung Mina Kuta - I Gede Antara Swenaya; I Made Darma Oka; I Ketut Astawa; Made Sudiarta; Dewa Made Suria Antara (International Journal of Glocal Tourism, 2022)
Purpose: This study aims to analyze the types of products that are suitable for development and to design a product development model for Warung Mina Kita in Kuta tourism area, Bali, Indonesia. Research methods: Data collection is sourced from participatory observation, interviews and focus group discussion. The data analysis technique uses an interactive analysis model from Miles and Huberman. Findings: The type of product developed by Warung Mina Kuta to meet customer needs was Mina Kuta special menu package consisting of appetizer (karedok), soup (fish head), main course (fried sea fish) and dessert (banana split). It emphasizes local products, which are named Mina Kuta Special Package Implication: The product process is carried out from preparing materials to raw materials being processed by a kitchen team headed by a chef, raw materials purchased from suppliers are materials that have grade A or good quality.